Odpowiedzi

Najlepsza Odpowiedź!
2009-10-29T19:26:11+01:00
Oblicz
a)4+3x+2x(do potęgi 2)+x(do potęgi 3) ,x= -√7
4+3x+2x²+x³ , x=-√7
4+3*√7+2*(√7)²+(√7)³=4+3√7+14+7=25+3√7


b) -2x(do potęgi 3) +x(do potęgi 2)+x-2 ,x= √5
-2x³+x²+x-2, x=√5
-2(√5)³+(√5)²+√5+2=-10+5+√5+2=17+√5
2009-10-29T19:32:28+01:00
A)4+3x+2x(do potęgi 2)+x(do potęgi 3) ,x= -√7

4+3x+4x(kwadrat)+x(sześcian)= 4+3*(-√7)+4*(-√7 do kwadratu)+(-√7 do sześcianu)=4+3*(-√7)+4*(-7)+(-7√7)=4+3*(-√7)-28-7√7=4-3√7-28-7√7=4-31-28-7=-62


b) -2x(do potęgi 3) +x(do potęgi 2)+x-2 ,x= √5

-8x(sześcian)+x(kwadrat)+x-2=-8*√5(sześcian)+√5(kwadrat)+√5-2=-40√5+5+√5-2=40√10+3=43√10